The Effectiveness Of Song On Increasing Student Motivation For Listening Comprehension In SMA 2 Langowan - Talumewo, Avelio Jeremi; Liando, Nihta V.F; Rombepajung, Paula (Program Studi Pendidikan Bahasa Inggris, 2025)
An action research project is this capstone project. The following problem statement serves to confine the debate in this study: